CONTRASTIVE ANALYSIS OF USING ACTIVE AND PASSIVE SENTENCE IN THE NOVEL OF â€œEAT, PRAY, AND LOVEâ€ BY MARGARET GILBERT - Haryani, Haryani; Hartanto, Cahya Fajar Budi (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
The objective of this study was to find out the differences and similarities of using passive voice in Source Text (ST) and translated them into Target Text (TT). The difference and similarity itself was found by comparing two sentences in two languages, between Indonesian and English which focused on using the passive voice sentences. Besides that, a descriptive qualitative method and contrastive analysis technique were used in analyzing 20% of data. The main results of the study were: the data that used active sentence in source language, and transfer it into active sentence (AA) was about 244 data (82 %). Next, the data from active sentence in source language and transfer it into passive sentences (AP) in target language was 45 (15 %). Moreover, the data from source language in the form of passive sentence and translated it into passive sentence (PP) in target language was 10 (3%). However, 0 (0%) data was in passive sentence and translated it into active sentence (PA).